Proceedings and debates of the Convention of North-Carolina (Printed by Hodge & Wills, printers to the State, 1789)
Proceedings and debates of the Convention of North Carolina in Hillsborough, which began on July 21, 1788, for the ratification of the United States Constitution. This journal, published in Edenton in 1789, contained the United States Constitution, the rules of the proceedings, the proposed Declaration of Rights and proposed amendments which were submitted to Congress
Evans, 22037
Keywords: Constitutions; Constitutional law; Constitutions - États-Unis - Ouvrages avant 1800; Droit constitutionnel - Ouvrages avant 1800; Politics and government; Early works